Factors influencing the green bond market expansion: Evidence from a multi-dimensional analysis - Chuc Anh Tu; Tapan Sarker; Ehsan Rasoulinezhad (Journal of Risk and Financial Management, 2020)
Expansion of green bond markets as an appropriate way to lower environmental pollution is one of the most debatable issues among scholars. However, the expansion of this market is not a simple matter and depends on several factors. The main purpose of this study is to carry out a multi-dimensional analysis using the analytic hierarchy process (AHP) method to find and prioritize factors influencing the development of green bond markets. As a case, we do our analysis for Vietnam that, since the last years, has been trying to expand green bond market as an effective investment channel to finance low-carbon projects. The main findings revealed that legal infrastructure, official interest rate of green bonds, and economic stability are the most important factors directly affecting green bond market expansion. Therefore, economic and legal requirements should be addressed by policy makers. As major policy implications, we recommend an affordable price of green bonds and improvement of economic and financial stability to accelerate the development of green bond markets.
Keywords: 330; green bonds; market expansion; analytic hierarchy process